(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article is devoted to the study of the specific features of improving product quality management in food industry enterprises. A brief description of the socio-economic environment of industrial enterprises is given to determine its necessary parameters. The priority aspects of product quality management in food enterprises discussed by the author were considered. The main directions of product quality management in such food industry enterprises are given.